Ultrasound Guided Core Needle Biopsy in The Diagnosis of Suspicious Breast Lesions: Radiologist’s perspectives - Aswad, Nabaa; Abedtwfeq, Raad Hefdhi (AL-Kindy College Medical Journal, 2023)
Background: Ultrasound guided core needle biopsy is becoming a gold standard in the work up of suspicious breast lesion. In Iraq, radiologists are not taking the lead in core needle biopsy performance.Objectives: To evaluate the radiologist performance of core needle biopsy highlighting the precession and accuracy of the procedure, the concordance of ultrasound and histopathology, and identifying challenges facing the radiologist during the procedure.Subjects and Methods: A prospective study involving a total of 50 patients with ultrasound (US) BIRADS IV or V.  Ultrasound guided core needle biopsy was performed for each patient. Surgical pathology diagnosis was available for 40 patients.  core needle biopsy results were correlated with Breast Imaging-Reporting and Data System (BI-RADS) categories and validity of the test was evaluated.Results: Malignancy was confirmed by histopathology in 76% of the cores. Concordance between BI-RADS(US) and histopathology for benignity and malignancy was achieved in all cores. Borderline lesions constituted 10% of total cores taken. Surgical resection of these lesions upgraded 3/5 (60%): two atypical ductal hyperplasia and an intraductal papillary lesions diagnosed by core needle biopsy found to be invasive ductal carcinoma after surgical resection.  Sensitivity of core needle biopsy in this study was 91.4% with 100% specificity. Positive and negative predictive values were 100% and 62.5% respectively. The underestimation rate in high-risk group was 3/5 (60%). No significant complication was reported.Conclusion:  Ultrasound guided core needle biopsy is a safe, efficient and relatively inexpensive method in diagnosing suspicious breast lesions. Radiologists can produce high sensitivity and specificity results.  Radio pathological correlation is of paramount in achieving accurate results.